Dietary inflammatory index, physical activity, body composition, and high sensitivity c-reactive protein levels in adolescent athletes in Central Java - Widyastuti, Trioni; Susanto, Hardhono; Noer, Etika Ratna; Muniroh, Muflihatul; Widyastiti, Nyoman Suci (Universitas Negeri Yogyakarta, 2024)
Inflammation is the body's response to tissue damage and infection. Prolonged inflammation can increase the risk of non-communicable diseases, including cardiovascular disease. Some factors that can trigger inflammation are dietary patterns, high physical activity, and body composition. This study examined the correlation between dietary inflammatory index (DII), physical activity, body composition, and high sensitivity C-reactive protein (hs-CRP) levels. It examined differences in characteristics based on gender. This study was a cross-sectional design of 55 adolescent athletes at the Student Sports Education and Training Center in Central Java. The exclusion criteria were an athlete who had a physical injury (did not participate in training) and a smoker. The DII score was calculated based on the dietary pattern using SQFFQ, anthropometric data (weight, height, and nutritional status based on BMI/age), body composition (body fat percentage, fat mass, and fat-free mass) using the BIA tool, physical activity data for the last seven days using IPAQ and hs-CRP levels using the FIA method. Our result showed that the DII score was significantly correlated with hs-CRP (p=0.013). There was no correlation between physical activity, body composition, and anthropometry with hs-CRP levels (p>0.05). There were differences in body height, body weight, body fat percentage, and fat-free mass between males and females (p<0.001). The diet of athletes had anti-inflammatory potential (83.6%), as evidenced by the intake of vitamins and minerals, and athletes had low hs-CRP levels <1 mg/L (85.5%), indicating that no inflammation occurred. Future longitudinal research is needed with a large population of adolescent athletes to explain the role of anti-inflammatory and pro-inflammatory diets on the incidence of inflammation and measure physical exercise in athletes to reduce inflammatory bias.